Literature Use in Iranian and International Journals of Applied Linguistics: A Grounded Theory Study - سیامک مرادی; عصمت بابایی; محمدرضا هاشمی (Journal of Applied Linguistics)
Researchers’ thorough familiarity with the related literature together with the appropriate implementation of previous studies in academic publications is of crucial importance. Simply put, scientific studies need to address the related literature in a proper manner to get published. The main objective of the current study was to delineate citation patterns in applied linguistics. To come up with a citation framework/typology for applied linguistics, the researchers employed constructivist Grounded Theory. In order to present a comprehensive picture of citation practices, the researchers decided to investigate a corpus of five international and two local journals published between 2015 and 2020. Initial results revealed 20 themes which were then further categorized into five major themes. The results revealed considerable discrepancies between the local and international studies in employing various citation forms which can be attributed to journal polices, target audience and researchers’ expertise level. Furthermore, differences were detected in quantitative and qualitative studies in using various citation techniques which can be associated with the nature of such studies.